2014
DOI: 10.3390/ijms150610350
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of NIPBL Physiological Splice Variants and Eight Splicing Mutations in Patients with Cornelia de Lange Syndrome

Abstract: Cornelia de Lange syndrome (CdLS) is a congenital developmental disorder characterized by distinctive craniofacial features, growth retardation, cognitive impairment, limb defects, hirsutism, and multisystem involvement. Mutations in five genes encoding structural components (SMC1A, SMC3, RAD21) or functionally associated factors (NIPBL, HDAC8) of the cohesin complex have been found in patients with CdLS. In about 60% of the patients, mutations in NIPBL could be identified. Interestingly, 17% of them are predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…To date 333 different heterozygous NIPBL mutations have been identified in 391 CdLS patients, 28 of whom belong to 13 families ; 278 of these mutations were compiled in an excellent recent review and subsequently 55 further novel mutations have been identified .…”
Section: The Genetic Basis Of Cdlsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date 333 different heterozygous NIPBL mutations have been identified in 391 CdLS patients, 28 of whom belong to 13 families ; 278 of these mutations were compiled in an excellent recent review and subsequently 55 further novel mutations have been identified .…”
Section: The Genetic Basis Of Cdlsmentioning
confidence: 99%
“…Small intragenic alterations account for the majority ( n = 267 unique mutations) of the NIPBL mutations: missense ( n = 81), nonsense ( n = 44), splice‐site mutations ( n = 59), regulatory ( n = 2) and deletions/insertions/duplications ( n = 116) . Most of these alterations are truncating mutations, which are shown or predicted to result in a partially functioning or a non‐functional truncated protein .…”
Section: The Genetic Basis Of Cdlsmentioning
confidence: 99%
“…The NIPBL gene is located at position 13.2 in the short arm of chromosome 5 (Figure 2a). Delangin protein encoded by NIPBL is an ortholog of Scc2 protein in Drosophila [1,11] and consists of 47 exons which are anticipated to construct six isoforms (Figure 3a) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In general, more damaging pathological variants (nonsense, frameshift) cause a more severe phenotype than less damaging pathological variants (missense) [10]. The NIPBL gene contains 47 exons and, although several transcripts have been identified in peripheral blood leukocytes [11], the main and largest size splicing variants are isoforms A and B. Both isoforms are conserved in vertebrates and have identical aminoacids from 1 to 2683, while the C-terminal ends are different [4].…”
Section: Introductionmentioning
confidence: 99%